Application of GIS : study of distribution of community hall in neighbourhood area in Seksyen 7, Shah Alam / Muhammad Haziq Ab Razak - Muhammad Haziq, Ab Razak (2020)
Community Hall is one of the requirement for community facilities, which is important to fulfill the basic for the people and as one of the needs in completing the needs of people. Community hall plays important part, for better understanding, to meet the current needs, potential role and to create a sustainable city in modern urban life. The strategic approach is needed to planning and managing the community hall to carry out its function and roles. This research aim to study specifically on the distribution of community hall and includes the population cap size of needs. This study is based on the data collected from survey and observation survey and secondary data, which is GIS data taken from iPLAN Malaysia@Selangor. The data was analysed to evaluate and study the distribution of community hall accordingly refer to the Garis Panduan Kemudahan Masyarakat, 2013 and using the Buffer Analysis in MapInfo. The findings from this analysis will be the basic preparation of make appropriate recommendations and conclusion. All the recommendations that has made are to develop a better community facilities in order to enhance the well-being of the neighbourhood in Seksyen 7, Shah Alam.